2022
DOI: 10.1021/acs.jmedchem.1c01732
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Orally Bioavailable Platelet-Derived Growth Factor Receptor (PDGFR) Inhibitors for the Treatment of Osteosarcoma

Abstract: Platelet-derived growth factor receptors (PDGFRs) are now considered promising targets for the treatment of osteosarcoma. Herein, the design, synthesis, and structure–activity relationships (SAR) of novel pyrimidine-2,4-diamine derivatives that selectively inhibit PDGFRα/β kinases have been studied. The screening cascades revealed that 7m was the preferred compound among these derivatives, with IC50 values of 2.4 and 0.9 nM for PDGFRα and PDGFRβ, respectively. Moreover, the 3-(4,5-dimethylthiazol-2-yl)-2,5-dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Additionally, platelets also have a great impact on the treatment of patients with osteosarcoma. For example, platelet-derived growth factor recepter can be used as a target for imatinib, mesylate, and other inhibitors in the treatment of osteosarcoma (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, platelets also have a great impact on the treatment of patients with osteosarcoma. For example, platelet-derived growth factor recepter can be used as a target for imatinib, mesylate, and other inhibitors in the treatment of osteosarcoma (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…186 Another study demonstrated that PDGFRC was overexpressed in triple-negative breast cancer patients and was associated with the patients' survival. 187 Additionally, after PDGFC and its receptors are inhibited, the drug effect of doxorubicin (DOX) can be enhanced, with more tumor apoptosis than only using DOX. 187 Nayeem et al discovered that PDGFRα was overexpressed in prostate cancer and the phosphorylation of this molecule and its downstream effector such as Akt was associated with tumorigenesis.…”
Section: Disruption Of the Crosstalk Between Platelets And Cancersmentioning
confidence: 99%
“…187 Additionally, after PDGFC and its receptors are inhibited, the drug effect of doxorubicin (DOX) can be enhanced, with more tumor apoptosis than only using DOX. 187 Nayeem et al discovered that PDGFRα was overexpressed in prostate cancer and the phosphorylation of this molecule and its downstream effector such as Akt was associated with tumorigenesis. However, the PDGFRα/Akt axis can be inhibited by Imatinib, a tyrosine kinase inhibitor, suppressing the growth and metastasis of tumor cells.…”
Section: Disruption Of the Crosstalk Between Platelets And Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacokinetic and In Vitro Metabolic StabilityStudy of Compound 5a. A preliminary pharmacokinetic (PK) study37 of compound 5a was performed by SAFE Pharmaceutical Technology Co., Ltd. (Beijing, China). BALB/ c mice were treated with compound 5a at doses of 5, 10, and 20 mg/kg body weight, and a 5a plasma concentration peaked 1 h after administration (Figure6A).…”
mentioning
confidence: 99%